Hoarseness in a child due to laryngopharyngeal reflux - Dantas, Ana (2011)
HOARSENESS IN A CHILD DUE TO LARYNGOPHARYNGEAL REFLUX Introduction: Symptoms associated with gastroesophageal reflux (GER) in children vary according to age. The prevalence ranges from 1,8% to 8,2%. The cardinal symptoms among older children and adolescents are heartburn and regurgitation. One possible complication is chronic hoarseness due to reflux laryngitis (laryngopharyngeal reflux - LPR). The goal of this case report is to alert physicians to the possibility of LPR/GER as a cause of chronic hoarseness in children. Case Report:We report the case of a six year old girl who consulted her general practitioner (GP) for a routine visit. The GP noticed hoarseness that her mother confirmed to be chronic. The girl was referred to an otorhinolaryngologist (ORL) who performed a nasopharyngolaryngoscopy. He found adenoid hypertrophy, right vocal fold edema and sulcus glottidis, and diagnosed LPR. The ORL prescribed esomeprazole and speech therapy. Nine months later the hoarseness was resolved. Comment: LPR caused trauma to the vocal folds resulting in hoarseness. Appropriate treatment resolved the symptoms. Hoarseness is insufficiently recognized by young patients, their parents and even by physicians. It may be the only symptom of LPR/GER. Failure to recognize it may delay diagnosis and treatment, increase complications and worsen prognosis.